Step
*
1
of Lemma
rv-line-circle-0
.....assertion..... 
1. n : ℕ
2. a : ℝ^n
3. b : ℝ^n
4. p : ℝ^n
5. q : ℝ^n
6. p ≠ q
7. d(a;p) ≤ d(a;b)
8. d(a;b) ≤ d(a;q)
⊢ ∃u:{u:ℝ^n| ab=au} 
   (real-vec-be(n;q;u;p)
   ∧ (∃v:{v:ℝ^n| ab=av} 
       (real-vec-be(n;q;p;v)
       ∧ ((d(a;p) < d(a;b)) 
⇒ (q-p-v ∧ ((d(a;b) < d(a;q)) 
⇒ q-u-p)))
       ∧ ((d(a;p) = d(a;b))
         
⇒ ((u ≠ v 
⇒ ((req-vec(n;u;p) ∧ (r0 < p - a⋅q - p)) ∨ (req-vec(n;v;p) ∧ (p - a⋅q - p < r0))))
            ∧ (req-vec(n;u;v) 
⇒ ((p - a⋅q - p = r0) ∧ req-vec(n;u;p))))))))
BY
{ ((Assert ((d(a;p) < d(a;b)) 
⇒ (||p - a|| < d(a;b))) ∧ (||p - a|| ≤ d(a;b)) BY
          ((Assert d(a;p) = d(p;a) BY Auto) THEN Fold `real-vec-dist` 0 THEN Auto))
   THEN (Assert ((d(a;b) < d(a;q)) 
⇒ (d(a;b) < ||q - a||)) ∧ (d(a;b) ≤ ||q - a||) BY
               ((Assert d(a;q) = d(q;a) BY Auto) THEN Fold `real-vec-dist` 0 THEN Auto))
   ) }
1
1. n : ℕ
2. a : ℝ^n
3. b : ℝ^n
4. p : ℝ^n
5. q : ℝ^n
6. p ≠ q
7. d(a;p) ≤ d(a;b)
8. d(a;b) ≤ d(a;q)
9. ((d(a;p) < d(a;b)) 
⇒ (||p - a|| < d(a;b))) ∧ (||p - a|| ≤ d(a;b))
10. ((d(a;b) < d(a;q)) 
⇒ (d(a;b) < ||q - a||)) ∧ (d(a;b) ≤ ||q - a||)
⊢ ∃u:{u:ℝ^n| ab=au} 
   (real-vec-be(n;q;u;p)
   ∧ (∃v:{v:ℝ^n| ab=av} 
       (real-vec-be(n;q;p;v)
       ∧ ((d(a;p) < d(a;b)) 
⇒ (q-p-v ∧ ((d(a;b) < d(a;q)) 
⇒ q-u-p)))
       ∧ ((d(a;p) = d(a;b))
         
⇒ ((u ≠ v 
⇒ ((req-vec(n;u;p) ∧ (r0 < p - a⋅q - p)) ∨ (req-vec(n;v;p) ∧ (p - a⋅q - p < r0))))
            ∧ (req-vec(n;u;v) 
⇒ ((p - a⋅q - p = r0) ∧ req-vec(n;u;p))))))))
Latex:
Latex:
.....assertion..... 
1.  n  :  \mBbbN{}
2.  a  :  \mBbbR{}\^{}n
3.  b  :  \mBbbR{}\^{}n
4.  p  :  \mBbbR{}\^{}n
5.  q  :  \mBbbR{}\^{}n
6.  p  \mneq{}  q
7.  d(a;p)  \mleq{}  d(a;b)
8.  d(a;b)  \mleq{}  d(a;q)
\mvdash{}  \mexists{}u:\{u:\mBbbR{}\^{}n|  ab=au\} 
      (real-vec-be(n;q;u;p)
      \mwedge{}  (\mexists{}v:\{v:\mBbbR{}\^{}n|  ab=av\} 
              (real-vec-be(n;q;p;v)
              \mwedge{}  ((d(a;p)  <  d(a;b))  {}\mRightarrow{}  (q-p-v  \mwedge{}  ((d(a;b)  <  d(a;q))  {}\mRightarrow{}  q-u-p)))
              \mwedge{}  ((d(a;p)  =  d(a;b))
                  {}\mRightarrow{}  ((u  \mneq{}  v
                        {}\mRightarrow{}  ((req-vec(n;u;p)  \mwedge{}  (r0  <  p  -  a\mcdot{}q  -  p))  \mvee{}  (req-vec(n;v;p)  \mwedge{}  (p  -  a\mcdot{}q  -  p  <  r0))))
                        \mwedge{}  (req-vec(n;u;v)  {}\mRightarrow{}  ((p  -  a\mcdot{}q  -  p  =  r0)  \mwedge{}  req-vec(n;u;p))))))))
By
Latex:
((Assert  ((d(a;p)  <  d(a;b))  {}\mRightarrow{}  (||p  -  a||  <  d(a;b)))  \mwedge{}  (||p  -  a||  \mleq{}  d(a;b))  BY
                ((Assert  d(a;p)  =  d(p;a)  BY  Auto)  THEN  Fold  `real-vec-dist`  0  THEN  Auto))
  THEN  (Assert  ((d(a;b)  <  d(a;q))  {}\mRightarrow{}  (d(a;b)  <  ||q  -  a||))  \mwedge{}  (d(a;b)  \mleq{}  ||q  -  a||)  BY
                          ((Assert  d(a;q)  =  d(q;a)  BY  Auto)  THEN  Fold  `real-vec-dist`  0  THEN  Auto))
  )
Home
Index